2014
DOI: 10.1016/j.jceh.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

HLA DRB1 Alleles Discriminate the Manifestation of Autoimmune Hepatitis as Type 1 or Type 2 in North Indian Population

Abstract: Background: Autoimmune hepatitis is a polygenic disorder of unknown etiology, where genetic factors affect the occurrence and clinical phenotype of the disease. It has been reported as a rare disease entity in the Indian subcontinent. This study was undertaken to investigate the association of HLA alleles with autoimmune hepatitis type 1 and type 2 in north Indian population and to analyze if distinct human leukocyte antigen (HLA) alleles help in characterization of the subtypes of autoimmune hepatitis. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Different risk alleles have been reported in other population cohort of patients with AIH type 1, confirming that there is a well‐identified inter‐population variability in HLA‐associated susceptibility …”
Section: The 81 Ah and Aidssupporting
confidence: 66%
See 1 more Smart Citation
“…Different risk alleles have been reported in other population cohort of patients with AIH type 1, confirming that there is a well‐identified inter‐population variability in HLA‐associated susceptibility …”
Section: The 81 Ah and Aidssupporting
confidence: 66%
“…28 Different risk alleles have been reported in other population cohort of patients with AIH type 1, confirming that there is a well-identified inter-population variability in HLAassociated susceptibility. [37][38][39][40][41][42][43] PSC and PBC are rare cholestatic liver diseases characterized by inflammation and fibrosis of intra-and extra hepatic bile ducts. PSC and PBC patients more frequently develop cirrhosis and require for liver transplantation.…”
Section: Autoimmune Liver Diseases: Autoimmune Hepatitis Sclerosinmentioning
confidence: 99%
“…In addition, several studies have shown that DRB1*04 : 04 , *04 : 05 , and *13 : 01 are associated with AIH in Latin America [ 10 , 11 , 12 , 13 ]. DRB1*08 alleles are also reported to be associated with AIH in Indian and Iranian, but not in Pakistani populations [ 14 , 15 , 16 ]. On the other hands, DRB1*15 : 01 is protective for the susceptibility of AIH in European and Japanese populations [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, DQB1*0201 is in a strong linkage disequilibrium with DRB1*07 and DRB1*03 . Moreover, the HLA DRB1*14 allele indicated a high risk of AIH‐2 in a north Indian population …”
Section: Exploration Of Susceptible Genesmentioning
confidence: 96%